Wzorzec przywódcy organizacji - Kolman, Romuald (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The above paper introduces the concept of criterial quality models. Process' projecting of the model of organization's leader has been presented with the final description of the model of universal use. The recommendations for use proposed in practice has been described. The article presents the evaluation examples including comments. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 108-116